A review of structural transformations and properties changes in starch during thermal processing of foods - Wang, Yi; Chen, Long; Yang, Tianyi; Ma, Yun; McClements, David Julian; Ren, Fei; Tian, Yaoqi; Jin, Zhengyu (Food hydrocolloids, 2021)
Starch is an important functional component in many foods and a major source of calories in the human diet. Steaming, cooking, extrusion, deep frying, stir-frying and baking, as the six traditional thermal treatments commonly used in starchy food processing, induce changes in the molecular architecture of starch granules, which alters their functional properties, such as their ability to thicken, gel, or stabilize foods. However, knowledge about how these traditional thermal treatments affect the structure and properties of starch during cooking is diffuse. In this paper, the mechanism of heat and mass transfer of traditional thermal treatments is reviewed, and their effects on the structure and functional properties of starch are discussed. Water phase (steaming, cooking, and extrusion), lipid phase (frying, stir-frying) and air phase (baking) thermal treatments are considered. The main structural changes induced by these treatments are gelatinization and retrogradation, which alter the textural properties of starchy foods, as well as their digestibility. This review provides a single resource that may be beneficial for those trying to control and improve the processing conditions of starchy foods. Finally, future developments and challenges in the thermal processing of starchy foods are highlighted. [Display omitted] •Effects of thermal treatments on structures and properties of starch are described.•Mechanisms of heat and mass transfer of traditional thermal treatments are reviewed.•The changes of starch in water phase, lipid phase and air phase are summarized.•Future development and challenge in thermal processing of starchy foods are discussed.